Faktor Faktor Yang Mempengaruhi Motivasi Kerja Pegawai Di Badan Pengembangan Sumber Daya Manusia - Risen Anugrah R; Budi Suharto; Nurlia Balqish (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This research aims at a). To know the factors that influence the motivation of employee work in the Human Resources Development Agency of Bengkulu Province. b) to be aware of factors that affect the level of individual characteristics with the motivation level of employee work. c). To determine the presence of factors that affect the level of occupational characteristics with the motivation level of employee work. D). To determine the factors that affect the characteristics of the working situation with the motivation of employee work. This research is a descriptive research analysis with a quantitative approach implemented by providing a list of questions relating to the research issues to the respondents. The Data analysis used in this study is a double linear regression analysis. The results showed that the individual characteristics, occupational characteristics, occupational situation characteristics positively and significantly affect the work motivation of the Human resources Development Agency. Where the motivation to increase the work of participants is 52% while the remaining 48% is influenced by other factors outside the study.